2017
DOI: 10.1371/journal.pone.0174463
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal symptoms in cystic fibrosis and their relation to genotype, history, clinical and laboratory findings

Abstract: Background & aimsAbdominal symptoms (AS) are a hallmark of the multiorgan-disease cystic fibrosis (CF). However, the abdominal involvement in CF is insufficiently understood and, compared to the pulmonary manifestation, still receives little scientific attention. Aims were to assess and quantify AS and to relate them to laboratory parameters, clinical findings, and medical history.MethodsA total of 131 patients with CF of all ages were assessed with a new CF-specific questionnaire (JenAbdomen-CF score 1.0) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 62 publications
6
81
1
2
Order By: Relevance
“…The finding of lipomatosis in our PS patients indicates an advanced stage in the progression from PS to PI. On the basis of a first and preliminary version of our score (JenAbdomen-CF Score 1.0) we demonstrated that PI-CF patients report significantly more GI symptoms compared to PS-CF patients 4 . A recent study using a symptom questionnaire developed as PI-specific patient-reported outcome measure (PROM) revealed that 84% of the patients reported experiencing abdominal pain 21 .…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The finding of lipomatosis in our PS patients indicates an advanced stage in the progression from PS to PI. On the basis of a first and preliminary version of our score (JenAbdomen-CF Score 1.0) we demonstrated that PI-CF patients report significantly more GI symptoms compared to PS-CF patients 4 . A recent study using a symptom questionnaire developed as PI-specific patient-reported outcome measure (PROM) revealed that 84% of the patients reported experiencing abdominal pain 21 .…”
Section: Discussionmentioning
confidence: 77%
“…The CFAbd-Score was further developed from our recently presented JenaAbdomen-CF Score 1.0 4 with additional 9 items concerning GI symptoms-related quality of life (QoL), thus now consisting of 26 items. QoL items were: embarrassed, physical activity limitation, reduced productivity, fatigue, reduced concentration, frustrated/restless/irritable, sad, difficulty falling asleep, and waking up at night, measured with a 6-point Likert scale from ‘not at all’ (0 pts) to ‘always’ (5 pts).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may also reflect the small sample size; since studies demonstrating a difference in gastrointestinal symptoms generally require larger sample sizes. 8,11,14,15 Our study illustrates that objective markers of gut function in CF may be more sensitive in detecting an abnormality than subjective symptom report. Further work is needed to determine whether these methods can also detect response to therapy in a smaller trial than would be needed to confirm effectiveness using a symptombased outcome.…”
Section: Discussionmentioning
confidence: 81%
“…Although all these symptoms associated to GIT is involved as a multiorgan manifestation, they have not yet been systematically quantified. Tabori et al [10] showed that patients with a severe course of the disease or with genotypes causing a moderate to severe abdominal involvement have more GI symptoms and that these symptoms are not associated with liver disease (CFLD) or elevated Liver Function Tests (LFTs).…”
Section: Introductionmentioning
confidence: 99%